Leaf extract of Garcinia atroviridis promotes anti-heat stress and antioxidant effects in Caenorhabditis elegans - Chuaijit, Sirithip; Punsawad, Chuchard; Winoto, Veronica; Plaingam, Waluga; Kongkaew, Itti; Phetcharat, Atidtaya; Ichikawa, Takafumi; Kubo, Makoto; Kawakami, Fumitaka; Tedasen, Aman; Chatatikun, Moragot (Frontiers in Pharmacology, 2024)
Introduction:Garcinia atroviridis has been used for traditional medicines, healthy foods and tea. The chemical compositions and biological activities of fruit, stem bark and root have been widely studied. However, the phytochemical components and the biological activities in Garcinia atroviridis leaves (GAL) are limited. This research aims to study the phytochemical components and the stress resistance effects of GAL in Caenorhabditis elegans (C. elegans). Methods: To investigate the chemical components and antioxidant activities of GAL extract, the ethanol extract was characterized by liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-QTOF MS) analysis and C. elegans was used to evaluate the effects of GAL extracts on longevity and stress resistance. Results and discussion: The results revealed that the ethanol extract of GAL possesses free radical scavenging activities. Furthermore, GAL extract increased the lifespan of C. elegans by 6.02%, 15.26%, and 12.75% at concentrations of 25, 50, and 100 μg/mL, respectively. GAL extract exhibited improved stress resistance under conditions of heat and hydrogen peroxide-induced stress. The survival rates of GAL extract-treated worms were significantly higher than those of untreated worms, and GAL extract reduced reactive oxygen species (ROS) accumulation. Additionally, GAL extract treatment upregulated the expression of stress resistance-associated genes, including gst-4, sod-3, skn-1, and hsp16.2. GAL extract supplementation alleviated stress and enhanced longevity by inducing stress-related genes in C. elegans. The observed effects of GAL extracts may be attributed to the stimulation of oxidant enzymes mediated through DAF-16/FOXO and SKN-1/NRF2, as well as the enhancement of thermal defense in C. elegans. Collectively, this study provides the first evidence of the antioxidant activities of GAL and elucidates the underlying mechanisms of stress resistance.